Interkulturalne kompetencije učenika osnovne škole u odnosu na njihova socio-pedagoška obilježja / Intercultural Competences of Elementary School Students in Relation to their Socio-Pedagogical Characteristics - Mikanović, Brane; Tomić, Marija (Pregled: časopis za društvena pitanja / Periodical for social issues, 2025)
Intercultural competences are one of the basic skills for the individual’s functioning in modern society. The constant need for rapid adaptation to changes and cooperation with members of other cultures, increasingly imposes the need for new patterns of behavior. Openness to differences, tolerance, communication skills and other determinants of interculturalism, become the basis for successful cooperation from an early age. Raising children to live and work in a multicultural environment is a matter of the current progress of the individual, but also future development of the wider social community. Possessing the competences to navigate and live in any ethnic, religious or national group is a condition for personal development but also for the progress of the entire society. The paper examines the self-assessment of intercultural competences of primary school students in relation to their gender, grade and school success. The data were collected using the intercultural competence scale. The results of the statistical analysis prove that higher results on the intercultural competence scale are achieved by female respondents, higher grade, and better school success. A statistically significant difference was shown in all three segments examined. Given that school success is a significant predictor of the examined competencies, the obtained results can be useful for the future direction of educational practice. By encouraging students to achieve better school success, we directly influence other segments of the personality that would contribute to the development of skills necessary for the individual's future. The obtained results leave space for further research into the causes of the identified differences.